From decisions to actions : trade as a catalyst for accomplishing the 2030 Agenda for Sustainable Development : executive summary (UN New YorkUS, 2017)
Considers that trade should support economic growth and be made socially and environmentally sustainable, with benefits spread across all segments of society.
Keywords: SUSTAINABLE DEVELOPMENT